Social Conformity in Solid Waste Management - Ranawake, A.P.; Wijesinghe, M.A.S.; Bandara, N.J.G.J. (University of Sri Jayewardenepura 2018, 2018)
The National Policy of Solid Waste Management (SWM) was publicised in Sri Lanka in the year 2007 with the aim to have waste-free Sri Lanka by 2011. However, the spread of Dengue epidemic and respiratory syndromes persuade the present investigation with objective to apprehend the effectiveness of SWM in terms of the National Policy of SWM empirically and to find out strategies that make the SWM more effective. The study used the inductive approach with Grounded Theory (GT) strategy and archival records and interview as data collection techniques covering entire Sri Lanka. Survey data and the secondary data were clustered together to process toward theorizing through open, axial selective coding. Results showed high Jaccard coefficients of 0.505 between concepts, the impact of People and Bureaucrats on SWM, 0.285 between the impact of Authorities and Citizens and 0.296 with the impact on Legal and Regulatory Framework. These results lead to construct a new social theory that explains the effectiveness of SWM varies with the level of persuasion and the social conformity of people and authority and the strength of legal framework. The theory explains that to achieve an effective SWM, persuasion can be used as an instrument under the background of effective law enforcement. The low effectiveness of SWM is related to the high Corruption Perception Index (CPI) attributed to Sri Lanka 95/162 by the Transparency International. The result explains the low effectiveness of SWM in other developing countries where CPI is high.
Keywords: 3-R principle, Developing countries, Environmental unconscious behaviour, National Policy of SWM, Legal Framework